Roadmap to mercury-free dentistry era: Are we prepared? - Sanchit Pradhan; Anupriya Srivastava (Wolters Kluwer Medknow Publications, 2022)
From the perspectives of longevity, mechanical performance, and economics, amalgam has long been considered the material of choice, especially for certain types of restorations in posterior teeth, including replacement therapy for existing amalgam fillings. In spite of numerous advantages over other filling materials, its use has been decreasing in recent years and the alternative tooth-colored filling materials are increasingly used. There is a trend towards minimal interventional, adhesive, techniques in dentistry, which are based on adhesion to tooth structure by chemical interaction and/or micromechanical retention. At the same time, the quality and durability of alternative materials have improved. Mercury is the metallic element of concern used in dental amalgam. Mercury is a well-documented toxicant, with reasonably well-defined characteristics for the major forms of exposure, involving elemental mercury as well as organic and inorganic mercury compounds. Looking into the kind of practice and its popularity among dentists and the patients in India, even we have to comply with the use of amalgam by implementing the best possible ways to minimize the extent of damage to nature.